Representasi Akhlak dalam Novel I am Sarahza Karya Hanum Salsabiela dan Rangga Almahendra serta Relevansinya dengan Pemelajaran Bahasa Indonesia di Madrasah Aliyah - Hilmi Mahya M.; Elen Inderasari (SUAR BETANG, 2019)
This study aims to represent the teachings of Islam on the moral aspects in the novel Iam Sarahza by Hanum Salsabiela and Rangga Almahendra published by Republika in 2018. Researchers also relevant the results of research by learning Indonesian in Madrasah Aliyah. This type of research is library research that is research conducted by collecting various literatures. Data collection techniques used are reading and note taking techniques. The validity of the data is obtained by using theory triangulation by collecting various relevant theories and then the researcher draws his conclusions, the researcher uses the perspective of more than one theory to discuss the problems examined in the form of intrinsic elements of literary works and Islamic teachings. the data analysis technique used is structuralism which is suitable for interpreting or describing Islamic teachings implicit in novel intrinsic elements. the results showed that the moral values contained in this novel include morals such as (1) polite, (2) sincere, (3) patient, (4) sympathizing orphans, (5) thanksgiving, (6) almsgiving, (7) advised, (8) throwing (9) trash in its place and (10) serving parents, and madzmumah's morals include (1) gossiping, (2) suicide, (3) drinking alcohol, (4) pessimism and (5) kufr. The results of the research related to the moral values can be implemented in learning Indonesian in madrasas.